2017
DOI: 10.1111/andr.12368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intralesional injection of hyaluronic acid compared with verapamil in Peyronie's disease: preliminary results from a prospective, double‐blinded, randomized study

Abstract: Several intralesional therapeutic protocols have been proposed for the treatment of Peyronie's disease. Among all, hyaluronic acid (HA) and verapamil have been differently tested. We aimed to evaluate the efficacy of intralesional verapamil (ILVI) compared with intralesional HA in patients with early onset of Peyronie's disease (PD). This is a multi-centre prospective double-arm, randomized, double-blinded study comparing ILVI vs. intralesional HA after 12-weeks. Sexually active men, older than 18 years and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…The comparative study by Favilla et al described previously in this paper also showed advantageous outcomes of HA when compared to verapamil therapy 47 .…”
Section: Hyaluronic Acidsupporting
confidence: 69%
“…The comparative study by Favilla et al described previously in this paper also showed advantageous outcomes of HA when compared to verapamil therapy 47 .…”
Section: Hyaluronic Acidsupporting
confidence: 69%
“…A final consideration is the comparative efficacy of IVI and other experimental therapies that have shown promise in the treatment of PD, including interferon alpha‐2b (Hellstrom et al, ) and hyaluronic acid (Zucchi et al, ). Studies have concluded that these treatments are comparatively better than verapamil in the improvement of certain outcomes (Favilla et al, ; Russo et al, , ). However, verapamil has a clear benefit over the first of these treatments: interferon alpha‐2b injection is associated with considerable side effects that IVI is not associated with (Wegner, Andresen, Knispel, & Miller, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies and a more recent prospective study have shown a reduction in penile plaque size and curvature, as well as improved penile rigidity. [52][53][54] Botulinum toxin has been shown to reduce fibrosis and scarring. A single study evaluated botulinum toxin A as a treatment for PD and has shown a positive response for safety and improvement in penile curvature, while data from further investigations is pending.…”
Section: Corticosteroidsmentioning
confidence: 99%